Proyecto de factibilidad para la creación de una empresa productora y comercializadora de leche pasteurizada en el cantón Lago Agrio, provincia de Sucumbíos, para el año 2015 - Ramírez Barragán, Glenda Elizabeth (2015)
The issue addressed in this study is of great importance for the production volume of existing raw material in the area, the lack of enterprises engaged in processing and the considerable demand for the product locally. The problem lies mainly in the external supply dependency on a staple as milk, it requires appropriate processes to ensure quality, this creates a dependency chain both in marketing and in its market cost. The aim of this thesis is the implementation of a producer and marketer of pasteurized milk in the canton Lago Agrio, Sucumbios, 2015, held in order to exploit the potential of Canton, being a place eminently livestock production. To carry out the following research methodology was used, deductive and inductive, accurate to analyze the facts in depth and establish the most relevant conclusions method was used, the analytic-synthetic, scientific, statistical and descriptive methods useful were also used for the application, understanding and demonstration of this work. It starts with market research; for that 381 surveys of the inhabitants of Lago Agrio Canton in order to know the level of acceptance of the product, in addition to the study of supply were applied were surveyed to 4 bidders supermarket dairy products, based on the information obtained he determined an unmet demand for 4.725.807 liters of pasteurized milk in its first year of project implementation.. Then the technical study, which determines the optimal location of the plant itself will be located in that parish was developed Sta. Cecilia km. 15 ½ route to Quito, it was determined that the company's installed capacity is 748.800 liters of pasteurized milk, will begin producing 80% of its installed capacity, that is 599.040 liters of pasteurized milk in their first year of operation. Subsequently the administrative study was conducted, and the need was determined with 10 people for the implementation of the project. In the economic study an investment of USD $259.201,66 Dollars of the United States of America is determined to start the project, the financial evaluation produced the following results VAN = USD $4.548,02 Dollars of the United States of America so it is accepted the project. IRR = 11.36%, acceptable, because the result is greater than the cost of capital rate of 11%. RECOVERY PERIOD: the investment is recovered in 6 years 1 month and 6 days. BENEFIT / COST RATIO = USD $1.17 Dollars of the United States of America, which means that for every dollar spent earns 17 cents. SENSITIVITY ANALYSIS, increasing costs to 9.53% and decreasing revenue to 8.16% resulting 0.99 less than 1; therefore the project is not sensitive to future changes in costs and income. Finally it is concluded that this study becomes a profitable project with good market expectations; and contribute to strengthening the economy of the area, create jobs, said raising the economic level of the population and thus improve their quality of life.